Comparision of performance between synchronous and asynchronous processors - Saini, Rachit (My University, 2018)
Up till past few years, the synchronous processors have been at the forefront in performance due to well established methodology and existence of tools to work with. However, the question remains whether it is possible to increase performance by applying some new methodology. One of the potential solutions to this issue is the use of asynchronous methodology. Asynchronous processors have been pondered over for producing result with lesser time and power consumption as compared to synchronous processors. In this thesis, the focus is on comparing the performance of synchronous processor and asynchronous processor. A synchronous processor operates as per a global clock whereas an asynchronous processor operates using the handshaking signals. The time required for computation for both methodologies is compared to prove effectiveness of asynchronous methodology over synchronous methodology. Both types of processors have same set of blocks, however, the way of execution of instructions in both the processors varies. Moreover, a hybrid of synchronous and asynchronous methodology is being utilized these days in order to capture the advantages of both the methodologies.
Keywords: Asynchronous; Synchronous; Methodology; Processor